An ethnographic research on the commercialization of the town of Baler, Aurora - GIO ANGELO B. ESCANILLAS (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: The purpose of this ethnographic study was to investigate how resorts and other tourist attractions have changed life in Baler, Aurora.Method: The effects of this